(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Shame highlights thenetwork of trancultural relationships between the individual and historicalforces and the prevailing politico-social situations in Pakistan and even thefate of the poet Omar Khayyam which is transcultural. Thus, Shame is a robust baroque incarnationof the political novel as a fable, a polemic excoriation as history or asfiction. Polemics is forceful verbal or written controversy or argument for oragainst something or somebody. In this context this novel can be treated as amyth, and also as satire. One can see Moorish Spain as a fusion of cultures -Spanish, Moorish, Jewish, the ’Peoples of the Book’ - which came apart at thefall of Granada. Camoens after flirting with Communism, becomes a Nehru man,dreaming of an independent, unitary India which he hopes will be ’abovereligion because secular, above class because socialist, above caste becauseenlightened.’ The narrator seems to be carried away often, as here also, theopened net windows of the house which not only let in the sights and sounds ofCochin Harbour but also the news about politics and society are let in.